Desarrollo de un modelo térmico de la fase volátil en un horno rotatorio mediante los métodos elementos y volúmenes finitos (2019)
In this research project a computational thermal modeling was carried out by means of finite elements and volumes, of the volatile phase present inside a rotary kiln used for the production of biofuels, which are obtained by indirect biomass heating. The biofuels products obtained are a friendly source of energy with the planet and the amounts obtained from each depend on the operating temperature of the furnace, since pyrolysis or gasification can occur and each of these processes generate different products. When performing the computer simulation, the temperature at which the volatile phase is found was found, in order to try to predict the thermal behavior inside the oven. Having this thermal model you can study the physical behavior of the volatile phase.